(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Innovative educational technology have transformed teaching and learning techniques. Higher education has recently begun to incorporate new technology as artificial intelligence advances. The purpose of this conceptual review article is to look into the rise of artificial intelligence in education teaching and learning. It investigates the educational implications of emerging technology on how schools educate and how students learn. The goal of this research is to forecast the role of artificial intelligence in the future of education in the globe. Artificial intelligence approaches that are used effectively are seen as a way to improve the quality of teaching and learning The difficulties of incorporating artificial intelligence in educational institutions, on the other hand, are addressed. Furthermore, the difficulties encountered artificial intelligence adoption by students in terms of student assistance, teaching, and learning The topics of governance and administration are explored. This article provides a short review of the most current research findings. research to illustrate how artificial intelligence may be used in educational settings The There are some suggestions for further study and consequences.